BILATERAL PROTRUSION OF FEMORAL HEAD INTO THE PELVIS IN NEGLECTED OSTEOMALACIA - Khan, Mohammad Shoaib; Sultan, Shahid; Khan, Alamzeb; Younis, Muhammad (Journal of Ayub Medical College Abbottabad, 2007)
Osteomalacia is a metabolic bone disease in a mature individual, caused by lack of vitamin D or its active metabolites, on account of a number of factors. Osteomalacia is common in females and in countries with less sun shine. It typically presents with body aches, weakness, alongwith signs of bone tenderness and proximal myopathy. Diagnosis is made on the basis of clinical presentation and investigations; serum calcium, phosphorus, serum alkaline phosphates, 24 hour urine for calcium and phosphorus andskeletal radiology. Key words: Osteomalacia; Bilateral; Pelvis; Femur